PENGARUH PENGGUNAAN GEL LIDAH BUAYA (Aloe Vera) PADA PEMBUATAN SABUN CAIR DENGAN PEWANGI MINYAK NILAM (Patchouli Oil) - Endo Pebri Dani Putra; Sahadi Didi Ismanto; Diana Silvy (Universitas Andalas, 2019)
This research was aimed to determine the effect of aloe vera gel to liquid soap moisturize activities of liquid soapto skin, and to determine the best addition of aloe vera gel. This research used a completely randomized design (CRD) consisting of 5 treatments and 3 replications. Data were analyzed statistically using ANOVA followed by Duncan test's New Multiple Range Test (DNMRT) at 5% level. Treatment in the present research is the addition of aloe vera gel at 0%; 6%; 7%; 8%; and 9%. Observations on the resulting liquid soap products were organoleptic, physical properties, chemical properties of soap, antimicrobial test, moisturize activities test, and irritation test. The physical propertiestest to soaps include viscosity, specific gravity and total foam. For chemical propertiestest to soaps include pH andfree alkali. The results showed that the difference in concentration of aloe vera gel to liquid soap significantly affected to viscosity, pH, antimicrobial and moisture activities of product and did not significantly affected to specific gravity, free alkali, and total foam. The best products based on organoleptic test on liquid soap was treatment B (addition of aloe vera gel 6%).